Preparation of in-situ formed TiN0.3-Ti5Si3-TiN composites through reactive spark plasma sintering of Ti and Si3N4. Issue 5 (1st April 2019) - Derakhshandeh, M.R.; Naeini, M. Soleymani; Ghasali, E.; Jam, A.; Fazili, A.; Alizadeh, M.; Kazemzadeh, A.; Ebadzadeh, T.
Abstract: In-situ intermetallic-ceramic composites have been prepared successfully via spark plasma sintering process using Ti and Si3 N4 starting materials. 5, 10 and 15 wt% of nano-sized Si3 N4 particles were mixed with Ti powders by milling in ethanol media for 2 h. Spark plasma sintering processes were performed at 1250 °C for each sample. It was observed that initial shrinkage of the sample with the lower amount of Si3 N4 took place at the earlier time and the total shrinkage of this sample was higher than the other samples due to lower refractoriness of this composite. The phase formation was investigated by XRD and FESEM analyses. XRD analysis showed that the TiN0.3 and Ti5 Si3 phases are formed for all samples after sintering process. It was also observed that in Ti-15%Si3 N4 sample, the third phase of TiN was formed due to increasing of the N concentration in the composite and formation of a concentrated solid solution of N in Ti (50 at%). By increasing the Si3 N4 content, the Ti5 Si3 amount was increased due to increasing of Si concentration in the composite. Finally, the hardness and flexural strength of the composites were examined by Vickers hardness and 3-point bending strength tests. The results showed that increasing the content of Si3 N4 in the composites leading to increasing of the hardness from 632 Hv to 1126 Hv due to formation of hard phases. Inversely, bending strength of the samples was decreased from 880 MPa to 710 MPa by increasing of Si3 N4 content in the composites due to increasing of the composite brittleness.